EFFECT OF SPACING AND NITROGEN LEVELS ON PRODUCTIVITY OF PEARLMILLET IN DRYLAND REGIONS - C. RADHA KUMARI (The Journal of Research ANGRAU, 2018)
Studies on response of pearlmillet (ABH-1) to spacing and nitrogen levels in alfisols of scarce rainfall zone under rainfed conditions revealed that plant height, DMP, number of panicles plant-1, panicle length, threshing percentage, grain yield, net returns and B:C ratio did not differ significantly due to spacing, however, pearlmillet sown at 60 cm x 15 cm produced higher growth, yield attributes, yield and economics. Application of 80 kg N ha-1 resulted in tallest plants and 60 kg N ha-1 produced higher drymatter production. Application of 100 kg N ha-1 produced higher leaf area and leaf area index, yield attributes, whereas, grain yield was higher with application of 60 kg N/ha and straw yield was higher with application of 80 kg N ha-1. Nitrogen levels did not influence panicle length and threshing percentage.